The Impact of Gymnastics Learning on the Endurance Improvement of Seventh Grade Students at State Junior High School 6 in Bengkulu City - Hidayah Mustika Canggih; Nuridin Widya Pranoto; Wilda Welis; Sayuti Syahara (JETL (Journal of Education, Teaching and Learning), 2025)
This research was conducted to address the low level of physical fitness, particularly VO₂Max, among junior high school female students, which impacts their overall health and physical performance. The objective of this study was to investigate the effect of poco-poco and SKJ 2021 aerobic exercise programs, along with the influence of exercise motivation, on the improvement of VO₂Max in female students at SMP Negeri 6 Bengkulu. The study employed a quantitative approach using a quasi-experimental method with a 2x2 factorial design. A total of 24 female students were selected through total sampling and divided into four treatment groups. The exercise was conducted over 12 sessions, and VO₂Max was measured using the Multistage Fitness Test (MFT). The results revealed that the group performing SKJ 2021 with high motivation (A2B1) achieved the highest average posttest VO₂Max score of 41.2 ml/kg/min, while the poco-poco group with low motivation (A1B2) had the lowest average score of 35.6 ml/kg/min. Two-way ANOVA analysis showed a significant effect of both exercise type and motivation level on VO₂Max (p < 0.05). The interaction between exercise and motivation was also statistically significant. These findings conclude that the combination of structured aerobic exercise and high motivation significantly enhances cardiovascular endurance in female junior high school students.